2015
DOI: 10.4103/0019-5154.160475
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia-Can it be ignored?

Abstract: Genus Malassezia comprises of 14 species of “yeast like fungi,” 13 of which are lipophilic and 1 is nonlipophilic. They are known commensals and in predisposed individuals they commonly cause a spectrum of chronic recurrent infections. They rarely also cause serious illnesses like catheter-related blood stream infections, CAPD associated peritonitis etc., Though these fungi have been known to man for over 150 years, their fastidious nature and cumbersome culture and speciation techniques have restricted resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 64 publications
2
16
0
1
Order By: Relevance
“…The current study revealed that the age group (15-22) years was frequently exposed to Malassezia infection, followed by (23-30) years age group.The age group (39-42) years was the minimally exposed to infection compared with other groups. This result come in accordance with that reported in India and Iraq by [17], [23], [24], [25], [26], [27], [28]. M. furfur was the predominant species recovered from PV cases while M. pachydermatis was the least once.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study revealed that the age group (15-22) years was frequently exposed to Malassezia infection, followed by (23-30) years age group.The age group (39-42) years was the minimally exposed to infection compared with other groups. This result come in accordance with that reported in India and Iraq by [17], [23], [24], [25], [26], [27], [28]. M. furfur was the predominant species recovered from PV cases while M. pachydermatis was the least once.…”
Section: Discussionsupporting
confidence: 92%
“…An inverse significant correlation was reported between age and exposure to Malassezia spp . Infection, which agrees with Al-ammari from Iraq and Thayikkannu et al, from India [20], [25].…”
Section: Discussionsupporting
confidence: 84%
“…9 However, Malassezia infections can manifest as superficial localized or can cause systemic infections in immune-compromised hosts. 10 Research suggests that immune response and inflammation show the presence of host susceptibility factors, allowing the transition of M furfur to its pathogenic form. 11…”
Section: Immunosuppresive Diseases and Pityriasis Capitismentioning
confidence: 99%
“… 30 Therefore, individual sensitivity to the irritating FFA determines the consequent inflammatory response and may define susceptibility for seborrheic dermatitis. 31 …”
Section: Sebum Alterations In Various Skin Diseasesmentioning
confidence: 99%